EFFICACY OF THE MANUAL THROMBOASPIRATION IN PATIENTS AFTER MYOCARDIAL INFARCTION WITH ACUTE ST SEGMENT ELEVATION - Besh, D.I. (World of Medicine and Biology, 2019)
ST segment elevation myocardial infarction (STEMI) is one of the major causes of death and disability in Ukraine as in other European countries. The purpose of the work was to study the efficacy of the manual thromboaspiration (MTA) in patients with STEMI and total occlusion or evident thrombosis of infarctrelated artery. The total of 200 patients with STEMI and total occlusion or evident thrombosis of infarctrelated artery were explored. Main group consists of 100 patients whose primary percutaneous coronary intervention (PCI) include MTA. Comparison group includes another 100 patients with conventional PCI. Baseline features of the patients from both groups were similar. Frequency of reaching ТІМІ 3 blood flow or MBG 3 after PCI didn’t differ significantly between patients (p>0.05 for both). Insignificant trends to better ST segment resolution (72% vs. 83%, р=0.063) and significant better ejection fraction of the left ventricle (48.34±9.39 vs. 52.57±10.44, р=0.003) were observed in the comparison group. Need for the balloon angioplasty was significantly lower in main group (49% vs. 82%, р
Keywords: myocardial infarction; thromboaspiration; coronary artery thrombosis